Maternal predator‐exposure affects offspring size at birth but not telomere length in a live‐bearing fish. Issue 4 (28th January 2020) - Monteforte, Stefano; Cattelan, Silvia; Morosinotto, Chiara; Pilastro, Andrea; Grapputo, Alessandro
Abstract: The perception of predation risk could affect prey phenotype both within and between generations (via parental effects). The response to predation risk could involve modifications in physiology, morphology, and behavior and can ultimately affect long‐term fitness. Among the possible modifications mediated by the exposure to predation risk, telomere length could be a proxy for investigating the response to predation risk both within and between generations, as telomeres can be significantly affected by environmental stress. Maternal exposure to the perception of predation risk can affect a variety of offspring traits but the effect on offspring telomere length has never been experimentally tested. Using a live‐bearing fish, the guppy ( Poecilia reticulata ), we tested if the perceived risk of predation could affect the telomere length of adult females directly and that of their offspring with a balanced experimental setup that allowed us to control for both maternal and paternal contribution. We exposed female guppies to the perception of predation risk during gestation using a combination of both visual and chemical cues and we then measured female telomere length after the exposure period. Maternal effects mediated by the exposure to predation risk were measured on offspring telomere length and body size at birth. Contrary to our predictions, we did not find a significant effect of predation‐exposure neither on female nor on offspring telomere length, but females exposed to predation risk produced smaller offspring at birth. We discuss the possible explanations for our findings and advocate for further research on telomere dynamics in ectotherms. Abstract : Telomere length could be a proxy for investigating the response to predation risk both within and between generations. We tested if the perception of predation risk could affect the telomere length of adult females and their offspring using the guppy, Poecilia reticulata, a live‐bearing fish. Contrary to our predictions, we did not find a significant effect of predation‐exposure neither on female mothers nor on offspring telomere length, but female mothers exposed to predation risk produced smaller offspring at birth.